Comparative analysis of diffusion length based on the volume scattering function measurements from the East and South China Seas - Han, Chang; Tao, Bangyi; Pan, Yaorui; Song, Qingjun; Huang, Haiqing; Mao, Zhihua (Frontiers in Marine Science, 2024)
Particle scattering is a key factor affecting underwater light transport. The diffusion length (z_D), defined as 1/[b(1-g)], where b is the scattering coefficient and g is the asymmetry factor, is obtained from the volume scattering function (VSF) of the particle and plays a vital role in assessing the potential for underwater optical detection, imaging and communication. Owing to the lack of VSF datasets, the variation in z_D at different wavelengths in various ocean areas remains unclear. In this study, we used a dual-wavelength (488 & 532 nm) VSFLab to conduct the VSF measurement experiments in the East China Sea (ECS) and the South China Sea (SCS), obtaining VSFs from 1.5° to 178.5° at 51 stations. Seven optical properties, including absorption (a), scattering (b), attenuation (c), diffuse attenuation coefficient (K_d), backscattering (b_b), g, and z_D, were calculated from the measured VSFs. A comparative analysis of the results was performed, which showed that the detection capability at 532 nm was better than that at 488 nm in terms of the absorption or diffuse attenuation coefficient in the ECS, whereas superior performance was observed at 488 nm in the SCS. However, from the perspective of scattering, z_D at 532 nm (z_D(532)) demonstrated superior performance in both the ECS and SCS. This superiority was particularly noticeable in regions with exceptionally clear water, such as the eastern side of the Luzon Strait, where z_D(532) exceeded z_D(488) by approximately 20%. Overall, the findings of this study provide a new perspective for assessing underwater light transmission capabilities.